2022
DOI: 10.1111/soru.12376
|View full text |Cite
|
Sign up to set email alerts
|

A call to expand disciplinary boundaries so that social scientific imagination and practice are central to quests for ‘responsible’ digital agri‐food innovation

Abstract: A call to expand disciplinary boundaries so that social scientific imagination and practice are central to quests for 'responsible' digital agri-food innovation INTRODUCTIONThe current venture capital investment model and associated start-up cultures require utmost positivity in technological investment, with 'success breeds success' being a common mantra in relation to university-industry partnerships (Santoro, 2000). Such approaches within the 'agtech' community result in existential challenges for those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…A critical social science approach to the political economy behind the financialization of space food research would also be of benefit. To conclude, when it comes to the technologies for growing food in space, whether it be Artificial Intelligence, machine learning, robotics and more, we agree with the recommendations noted by Fielke et al (2022). Fielke et al (2022) identified the need to expand disciplinary boundaries to ensure that social scientific imagination and practice are central in the quest for responsible for digital innovation.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…A critical social science approach to the political economy behind the financialization of space food research would also be of benefit. To conclude, when it comes to the technologies for growing food in space, whether it be Artificial Intelligence, machine learning, robotics and more, we agree with the recommendations noted by Fielke et al (2022). Fielke et al (2022) identified the need to expand disciplinary boundaries to ensure that social scientific imagination and practice are central in the quest for responsible for digital innovation.…”
Section: Discussionmentioning
confidence: 53%
“…To conclude, when it comes to the technologies for growing food in space, whether it be Artificial Intelligence, machine learning, robotics and more, we agree with the recommendations noted by Fielke et al (2022). Fielke et al (2022) identified the need to expand disciplinary boundaries to ensure that social scientific imagination and practice are central in the quest for responsible for digital innovation. Our study calls for the responsible framing of agri-food space technological innovations in news media, and the contributions of more social scientists in research and conversations around producing food in space.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Also, my proposal must not be misconstrued as propagation of primacy of technological innovations evident in current food regimes (Anderson et al, 2019) nor a presentation of digitalization as an uncontestable transformative solution to smallholder issues. Further scholarly inputs from diverse theoretical and analytical approaches, including responsible innovations (Klerkx and Rose, 2020;Fielke et al, 2022;Jakku et al, 2022) and the political economy of digitalization (Carolan, 2020;Duncan et al, 2021;Abdulai, 2022) is critical to ensuring the phenomenon does not reinforce existing inequalities. Digital transformations cannot happen without careful analysis of the political and economic implications of the phenomenon, including for rural communities and smallholders (Carolan, 2017;Rotz et al, 2019;Abdulai, 2022).…”
Section: Concluding Reflectionsmentioning
confidence: 99%